2010
DOI: 10.1055/s-0030-1250256
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine, the Main Alkaloid Component ofSophoraRoots, Protects Heart against Arrhythmias in Rats

Abstract: Oxymatrine is one of the main alkaloid components extracted from SOPHORA roots and has been shown to play various protective roles in the cardiovascular system. The present study was designed to study the protective effect of oxymatrine on arrhythmias and their ionic channel mechanism. Rat arrhythmic models were established by aconitine injection and coronary artery ligation. Rat cardiomyocytes were acutely isolated, and the whole-cell patch clamp technique was employed to investigate the effects of oxymatrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Electrophysiological studies indicated that oxymatrine could inhibit sodium and calcium currents in isolated rat cardiomyocytes in a concentration-dependent manner. Furthermore, oxymatrine significantly delayed the initial time and shortened the duration time of rat arrhythmias induced by coronary artery ligation [24]. …”
Section: Alkaloidsmentioning
confidence: 99%
“…Electrophysiological studies indicated that oxymatrine could inhibit sodium and calcium currents in isolated rat cardiomyocytes in a concentration-dependent manner. Furthermore, oxymatrine significantly delayed the initial time and shortened the duration time of rat arrhythmias induced by coronary artery ligation [24]. …”
Section: Alkaloidsmentioning
confidence: 99%
“…Compared with DMSO treated group, the expression levels of PCNA and Ki67 were significantly increased in PDGF-BB induced MOVAS cells, but this increment was dampened by OMT treatment ( Figure 2C). (0,5,10,20,40 …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that OMT shows a wide-range of pharmacological effects, including anti-inflammatory, anticancer, antiviral and immunomodulatory effects [14,[16][17][18][19]. In recent years, the cardio-protective effects of OMT are becoming more and more arresting, and it has been used to treat cardiovascular diseases via anti-arrhythmic effect, vasodilative activity, hypolipidemic, positive inotropic effect and resistance of ventricular remodeling [20][21][22][23][24][25]. However, whether OMT exerts pharmacological effect on PDGF-BBinduced MOVAS (a mouse vascular aortic smooth muscle cell line) proliferation is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…It ameliorates the experimental ventricular remodeling by reducing serum content of asymmetric dimethylarginine (ADMA), increasing double methyl arginine hydrolase 2 antibodies (DDAH2) expression, 21 and inhibiting the expression of angiotensin-converting enzyme (ACE) and TGF-β1 and activation of extracellular signalregulated kinase 1/2 (ERK 1/2), Jun N-terminal kinase (JNK), and p38 MAPK signaling pathways. 22 Oxymatrine acts against excessive aldosterone-induced cardiotoxicity through inhibition of calpain/apoptosis-inducing factor signaling pathways, 23 improves heart failure by upregulation of sarcoplasmic reticulum Ca2+ ATPase and dihydropyridine receptor, 24 protects arrhythmias through inhibition of sodium and calcium currents, 25 and shortens the action potential duration through reduction of L-type calcium current, enhances transient outward potassium current, and inhibits inward rectifier potassium current. 26 …”
Section: Cardiovascular Protective Effectmentioning
confidence: 99%